DOWNREGULATION OF STEAROYL-COA DESATURASE 1 (SCD-1) PROMOTES RESISTANCE TO IMATINIB IN CHRONIC MYELOID LEUKEMIA - Buket Altinok Gunes; Yalda Hekmatshoar; Tulin Ozkan; Sureyya Bozkurt; O.Sena Aydos; Yahya Buyukasik; Elifcan Aladag; Asuman Sunguroglu (Mediterranean Journal of Hematology and Infectious Diseases)
Chronic myeloid leukemia (CML) is a malignant hematopoietic stem cell disease resulting in the fusion of BCR and ABL genes and characterized by the presence of the reciprocal translocation t(9;22)(q34;q11). BCR-ABL, a product of the BCR-ABL fusion gene, is a structurally active tyrosine kinase and plays an important role in CML disease pathogenesis. Imatinib mesylate (IMA) is a strong and selective BCR-ABL tyrosine kinase inhibitor. Although IMA therapy is an effective treatment, patients may develop resistance to IMA therapy over time. This study investigated the possible genetic resistance mechanisms in patients developing resistance to IMA. We did DNA sequencing in order to detect BCR-ABL mutations, which are responsible for IMA resistance. Moreover, we analyzed the mRNA expression levels of genes responsible for apoptosis, such as BCL-2, P53, and other genes (SCD-1, PTEN). In a group of CML patients resistant to IMA, when compared with IMA-sensitive CML patients, a decrease in SCD-1 gene expression levels and an increase in BCL-2 gene expression levels was observed. In this case, the SCD-1 gene was thought to act as a tumor suppressor. The present study aimed to investigate the mechanisms involved in IMA resistance in CML patients and determine new targets that can be beneficial in choosing the effective treatment. Finally, the study suggests that the SCD-1 and BCL-2 genes may be mechanisms responsible for resistance.